2003
DOI: 10.1016/s0741-5214(02)75332-9
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of polytetrafluoroethylene bypass grafts to infrapopliteal arteries1 1Competition of interest: none.Additional material for this article may be found online at www.mosby.com/jvs.

Abstract: This meta-analysis indicated moderate success for PTFE bypass grafts to infrapopliteal arteries, but the role of adjunctive procedures at the distal anastomosis remains uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(22 citation statements)
references
References 64 publications
(133 reference statements)
0
20
0
Order By: Relevance
“…Autologous vein bypass grafts, the gold-standard of care, cannot always be harvested, prompting the use of prosthetic vascular grafts. However, prosthetic vascular grafts have poor long-term patency, particularly when used in small diameter applications [1,2]. Therefore, there remains an urgent need for safe and effective materials for the fabrication of vascular grafts.…”
Section: Introductionmentioning
confidence: 99%
“…Autologous vein bypass grafts, the gold-standard of care, cannot always be harvested, prompting the use of prosthetic vascular grafts. However, prosthetic vascular grafts have poor long-term patency, particularly when used in small diameter applications [1,2]. Therefore, there remains an urgent need for safe and effective materials for the fabrication of vascular grafts.…”
Section: Introductionmentioning
confidence: 99%
“…5 - 7 Unfortunately, longer prosthetic grafts do not always perform as well as noted in several retrospective series. 8-10 …”
Section: Introductionmentioning
confidence: 99%
“…Arm veins or polytetrafluoroethylene (PTFE) grafts with adjunctive procedures could be considered as alternative bypass conduits when all saphenous veins are inadequate for LEAB bypass [18]. Previous studies showed that results from infrapopliteal bypass using prosthetic graft have been less satisfactory than those obtained with arm vein (Table 4) [8,12,16,1925].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, subanalysis of infrapopliteal arm vein bypasses (23 cases) showed that 3-year primary patency, secondary patency, and limb salvage rates were 50.5%, 63.3%, 92.9%, respectively. By comparison, a meta-analysis of PTFE infrapopliteal bypass published in 2003 introduced 3-year primary patency, secondary patency, and limb salvage rates of 41%, 51%, and 66%, respectively [18]. The above results suggest that the arm vein is a favorable alternative conduit in infrapopliteal bypass when no saphenous veins are available.…”
Section: Discussionmentioning
confidence: 99%